Design strategy of TiC reinforced heterogeneous Ti-composites with an induced <c + a> slip system for achieving high strength-ductility - Longlong Dong; Yan Tang; Wendian Fan; Xiang Li; Junjie Xu; Guodong Sun; Mingjia Li; Yongqing Fu; Ahmed Elmarakbi; Lianwen Wang; Yusheng Zhang (Materials Research Letters, 2024)
Achieving high strength and ductility for Ti alloys and their composites has been a key objective and also a great challenge for their engineering applications. Herein, we designed TiC/(TC18 + TC4) composites with bionic and heterogeneously lamella structures, achieving an exceptional combination of high strength and ductility. This is attributed to the formation of alternative layers of TC18-coarse grains and TC4-fine grains with TiC precipitated at their interfaces. Plastic incompatibility of these three-phases produces significant hetero-deformation-induced hardening, induced by mutual interactions of heterogeneous grains and TiC precipitates, as well as activation of extensive < c + a > slip groups. An optimal yield strength of ∼ 1168 MPa and a uniform elongation of ∼ 6% have been achieved, which are much higher than those of the TC4 matrix (i.e. ∼919 MPa and ∼2%). This study provides a new strategy for composite designs to overcome the trade-off dilemma for strength-ductility.